Working with water harvesting and terracing in Lower Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East African regional program has selected six sites to test interventions that address risks related to climate change and variability. Featured here is the Lower Nyando, Kenya site, where farmers harvest rain water and use it for various farming activities. Additionally, the farmers have taken up terracing to protect their crops from excess rain water. Photo: K. Trautmann Please credit accordingly.